Immuno-expression analysis of VEGF and CD34 related to histological types of mandibular ameloblastoma - Pradana, Septian; Kamadjaja, David Buntoro; Danoediningrat, Coen Pramono; Sumarta, Ni Putu Mira; Amir, Muhammad Subhan; Rahayu, Retno Pudji; Bhagat, James Antony (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Increased expression of vascular endothelial growth factor (VEGF) and cluster of difference 34 (CD34) in ameloblastoma has been noted. Both proteins are markers of angiogenesis that play a role in supporting the growth of ameloblastoma. The existence of histopathological types of ameloblastoma allows for differences in behavioral and growth characteristics. Purpose: To evaluate the differences and correlation of VEGF and CD34 expression in histological types of ameloblastoma. Methods: This laboratory cross-sectional study uses total sampling from histological slides of mandibular ameloblastoma. Two observers manually quantified the immunohistochemical expression. The comparative data were analyzed statistically with the Kruskal–Wallis test (p < 0.05), while the correlative data were analyzed with Spearman’s rho (p<0.01). Results: 32 samples were obtained according to the inclusion criteria. The Kruskal–Wallis test showed significant differences in VEGF expression (p = 0.003) and CD34 expression (p = 0.026). The pairwise comparison test showed that VEGF expression in follicular ameloblastoma significantly differed from plexiform (p = 0.001) and combination (p = 0.002). The pairwise comparison test for CD34 expression showed a significant difference between follicular and combination ameloblastoma (p = 0.007). Spearman’s rho test showed a positive correlation (p = 0.001, r = 0.565) between markers. Conclusion: Follicular ameloblastoma expressed higher VEGF than plexiform and combination ameloblastoma. Follicular ameloblastoma expressed higher CD34 than combination types. CD34 expression is associated with VEGF in histological types of ameloblastoma.